The Representation of Basuki Tjahaja Purnama and Anies Baswedan in The Guardian and The Times’ Articles of Unofficial Quick Count Results of Jakarta Governor Election - Dian Kurniawati (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2019)
The aim of this paper is to present a critical discourse approach to compare two articles about unofficial quick count results of Jakarta Governor Election in The Guardian and The Times. Firstly, I will begin with the background analysis of why this issue is investigated and then I will explain how The Guardian and The Times represent social actors, social actions and visual representation of the social actors in their articles. Finally, I will discuss the content evaluation of these articles and end it with a conclusion. It can be concluded that both The Guardian and The Times use similar representational strategy to represent the main social actors. In their articles, Basuki Tjahaja Purnama is more activated and more prioritised despite being overtly described as a minority.